Mitigating the impact of COVID-19 on oncology: Clinical and operational lessons from a prospective radiation oncology cohort tested for COVID-19. (July 2020) - Ning, Matthew S.; McAleer, Mary Frances; Jeter, Melenda D.; Minsky, Bruce D.; Ghafar, Robert A.; Robinson, Ivy J.; Nitsch, Paige L.; Zaebst, Denise J.; Todd, Sarah E.; Nguyen, Jennifer; Lin, Steven H.; Liao, Zhongxing; et al.
Highlights: Prospective cohort of 121 cancer patients tested for SARS-CoV-2 over 35 days. Of 7 positive cases, 6 were admitted with 4 warranting intensive care, and 2 died. RT was delayed in one-third of patients while awaiting RT-PCR test results. With a dual PPE policy, newly quarantined employees decreased 6-fold per day. Each patient was an exposure risk to 5 employees, most commonly RTTs (38%) Abstract: Background and purpose: The COVID-19 pandemic warrants operational initiatives to minimize transmission, particularly among cancer patients who are thought to be at high-risk. Within our department, a multidisciplinary tracer team prospectively monitored all patients under investigation, tracking their test status, treatment delays, clinical outcomes, employee exposures, and quarantines. Materials and methods: Prospective cohort tested for SARS-COV-2 infection over 35 consecutive days of the early pandemic (03/19/2020–04/22/2020). Results: A total of 121 Radiation Oncology patients underwent RT-PCR testing during this timeframe. Of the 7 (6%) confirmed-positive cases, 6 patients were admitted (4 warranting intensive care), and 2 died from acute respiratory distress syndrome. Radiotherapy was deferred or interrupted for 40 patients awaiting testing. As the median turnaround time for RT-PCR testing decreased from 1.5 (IQR: 1–4) to ≤1-day ( P < 0.001), the median treatment delay also decreased from 3.5 (IQR: 1.75–5) to 1 business day (IQR: 1–2) [ P < 0.001]. Each patient was an exposure risk to a median of 5 employees (IQR: 3–6.5) through prolonged close contact. During this timeframe, 39 care-team members were quarantined for a median of 3 days (IQR: 2–11), with a peak of 17 employees simultaneously quarantined. Following implementation of a "dual PPE policy, " newly quarantined employees decreased from 2.9 to 0.5 per day. Conclusion: The severe adverse events noted among these confirmed-positive cases support the notion that cancer patients are vulnerable to COVID-19. Active tracking, rapid diagnosis, and aggressive source control can mitigate the adverse effects on treatment delays, workforce incapacitation, and ideally outcomes.